The Effectiveness of Thai Women Empowerment Funds Policy Implementation in Bandanlanhoi District, Sukhothai Province - Mingchua, Jeerapa; Rojanatrakul, Tanastha (Journal of Modern Learning Development, 2021)
The objectives of this research were: 1. Level of effectiveness in implementing the Women Roles Development Fund policy; 2. Factors related to the effectiveness of the implementation of the Women Roles Development Fund policy; Effectiveness of Implementation of the Women Role Development Fund Policy in Ban Dan Lan Hoi District Sukhothai It is a quantitative research. The samples used in this research were working groups, fund members, heads of government agencies, and professional groups. In Ban Dan Lan Hoi district The number of 293 people in Sukhothai was represented in Taro Yamane’s formula. Results of the Research 1. Overall, the level of the effectiveness of Thai women empowerment funds policy implementation in Bandanlanhoi District, Sukhothai Province was at the high level. 2. The factors having the relationship to the effectiveness of Thai women empowerment funds policy implementation in Bandanlanhoi District, Sukhothai Province had the positive relationship at the middle level (r = 0.510). 3. The guidelines for the factor management affecting to the effectiveness of Thai women empowerment funds policy implementation in Bandanlanhoi District, Sukhothai Province were that the management should reduce the steps of the approval process for the conciseness and rapidity and increase the manpower sufficient to the working. Moreover, the policy implementation should be clear, have the measure for promoting and supporting the working of Thai women empowerment funds, specify the role and responsibility of the local government organizations in Thai women empowerment funds, build the organizational networks, and integrate the working of the public and private organizations in promoting and supporting the policy drive of Thai women empowerment funds continuously.